Damage Evaluation in Tempered Vacuum Glazing via Multivariate Statistical Methods - Xiaobo Xi; Jiawen Xu; Jingyun Yuan; Yifu Zhang; Baofeng Zhang; Ruihong Zhang (Applied Sciences, 2021)
The performance of tempered vacuum glazing (TVG) strongly depends on the structural parameters and degree of damage of the products. In this paper, attention was paid to six performance indicators which had a major influence on the damage of TVG, and new evaluation parameters were derived from them using principal component analysis (PCA). In particular, hierarchical clustering analysis (HCA) based on Euclidean distance measurement enabled TVG products to be classified into three kinds. Considering the results of PCA, product quality classification was established according to the degree of damage. The evaluation method proposed in this work was found to be simple and reliable to provide references for damage detection of TVG.